172k views
1 vote
Solve for a: a/2 - 2/3 = a + 1/5

User Demarco
by
5.5k points

2 Answers

6 votes
Combining like terms, move the one with coefficient a to the left, and move the constant to the right

(a)/(2) - (2)/(3) =a+ (1)/(5)

(a)/(2) - a =(1)/(5) + (2)/(3)

equalize the denominators in like-terms

(a)/(2) - (2a)/(2) =(1 * 3)/(5 * 3) + (2 * 5)/(3 * 5)

(a)/(2) - (2a)/(2) =(3)/(15) + (10)/(15)

do the operation to the numerators

(-a)/(2) =(13)/(15)

solve for a
-a =
(13)/(15) * 2
-a =
(26)/(15)
a =
- (26)/(15)
User Peter Centellini
by
6.0k points
5 votes
the answer is 4 if I am correct
User Jan Marek
by
5.5k points